2019
DOI: 10.1111/jpc.14670
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants and causes of child mortality in Pakistan: Analysis of national demographic health surveys from 1990 to 2013

Abstract: Aim The aim of the study was to define social determinants, causes and trends in child mortality from 1990 to 2013 in Pakistan. Understanding social determinants, causes and temporal trends in child mortality can inform strategies aimed at improving child health in low and middle income countries. Methods We characterised temporal trends and social determinants of child mortality in Pakistan using national demographic health survey data (1990–1991, 2006–2007 and 2012–2013). We analysed national data to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 16 publications
(24 reference statements)
2
22
1
Order By: Relevance
“…provide life support to neonates; however, admission to an NICU entails risks for both families and their admitted infants, including high costs. [1,2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…provide life support to neonates; however, admission to an NICU entails risks for both families and their admitted infants, including high costs. [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…The efficient health care services of a country are categorized from neonatal morbidity and mortality [1,2]. Studies reported around 3 million mortality in neonates observed during this period, amounting to total of 45% of under-five deaths worldwide [1,3]. According to World Health Organization (WHO), 2015 nearly 2.7 million children died globally in the neonatal period, contributing to 45% of the total (under five mortality).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though many studies have identified a wide array of risk factors of child mortality such as size of child at birth [23] and women empowerment [24], antenatal care visit [25], our criterion for including the confounding variables was that they should be associated with both the HRFB and child mortality. As only those confounding factors can be appropriate for this study which occurred before the HRFB and, by implication, before the birth of the index child, size of child at birth, antenatal care visits and women's empowerment are, therefore, not included in the list of confounding factors.…”
Section: Potential Confoundersmentioning
confidence: 99%
“…Though many studies have identified a wide array of risk factors of child mortality such as size of child at birth [23] and women empowerment [24], antenatal care visit [25], our criterion for including the confounding variables was that they should be associated with both the HRFB and child mortality. As only those confounding factors can be appropriate for this study which occurred before the HRFB and, by implication, before the birth of the index child, size of child at birth, antenatal care visits and women's empowerment are, therefore, not included in the list of confounding factors.…”
Section: Potential Confoundersmentioning
confidence: 99%